Fenomena Thrift Shop Dikalangan Remaja: - Nella Linggar Adji; Dyva Claretta (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
This study examines how the phenomenon of shopping for imported used clothes is still suitable for use, which is commonly known as thrift. Many teenagers, especially in Surabaya, are interested in thrifting activities at their favorite thrift shop. This habit gives rise to a new culture commonly known as popular culture, a trend that is currently emerging, favored and created by the community. The purpose of this study was to find out how the understanding, experience, and motivation of the community, especially among Surabaya teenagers regarding the "Thriftshop" phenomenon. The research method used is a qualitative type with a phenomenological approach. This study uses Alfred Schutz's phenomenological theory. From the results of this study it can be concluded that the thrift shop phenomenon has many enthusiasts who come from among teenagers. There are various motivations behind why teenagers are more interested in shopping and using thrift shop clothes. That is to support the style of dress, the goods sold in the thrift shop have relatively cheap prices, besides that, by shopping at the thrift shop, teenagers can get good, unique (limited edition) goods or clothes. branded. Keywords: Thrift Shop, Popular Culture, Phenomenology, Youth